ISLAMIC MICROFINANCE AND POVERTY ALLEVIATION PROGRAM: PRELIMINARY RESEARCH FINDINGS FROM INDONESIA - Yasushi Suzuki; Sigit Pramono; Rufidah Rufidah (Share: Jurnal Ekonomi dan Keuangan Islam, 2016)
Poverty should be defined, measured, and scrutinized its root causes from a multi-dimension perspectives. Therefore, in designing and implementation of poverty alleviation program, it should consider economic factors, social and political contexts surrounding the poor. Sen (1982; 1999) views poverty as a multifaceted world and ethical dimension essentially should be placed underpinning it as a vital economic problem. The paper takes the stance that the poor themselves have potential capacity to alleviate their condition in resolving poverty trap. Community development program is one of the strategies to deal with the poverty problem. Islamic microfinance can play an important role in combating poverty dilemma especially in Muslim majority population communities. Through the approach proposed by Bigg and Satterthwaite (2005) with strengthening local organizations and community development programs, Islamic microfinance should engage a strategic partnership with the Masjid and Islamic charity institutions (zakat and waqf organization). This strategic alliance will result more integrated programs and also capacity building of the institutions involved. This paper aims to contribute a grass root model in the purpose of combating poverty in the framework of Islamic economic system. =========================================== Kemiskinan harus didefinisikan, diukur, dan diteliti akar penyebabnya dari berbagai perspektif. Oleh karena itu, dalam merancang dan mengimplementasikan program pengentasan kemiskinan, faktor-faktor ekonomi, konteks sosial dan politik yang mengelilingi kemiskinan juga harus dipertimbangkan. Sen (1982; 1999) memandang kemiskinan sebagai sebuah dunia yang kompleks, dan dimensi dasar etika harus ditempatkan sebagai sebuah masalah ekonomi yang vital. Peneliti sendiri dalam hal ini berpandangan bahwa orang-orang miskin pada dasarnya punya kapasitas yang memadai untuk keluar dari garis kemiskinan. Salah satunya adalah dengan program pengembangan masyarakat yang merupakan satu strategi dalam pengentasan kemiskinan. Keuangan mikro syariah dapat memainkan peran penting dalam memerangi dilema kemiskinan, khususnya di daerah-daerah yang mayoritas penduduknya Muslim. Pendekatan yang diusulkan oleh Bigg dan Satterthwaite (2005) adalah dengan cara penguatan organisasi lokal dan program pengembangan masyarakat dimana keuangan mikro syariah harus terlibat dalam kemitraan-kemitraan strategis dengan masjid-masjid dan lembaga-lembaga sosial lainnya (seperti lembaga zakat dan wakaf). Aliansi strategis ini akan menghasilkan program-program yang lebih terintegrasi dan juga ada penguatan capacity building dari lembaga-lembaga yang terlibat. Makalah ini bertujuan untuk berkontribusi dalam memberikan model akar rumput dalam hal pengentasan kemiskinan dalam kerangka sistem ekonomi Islam.